Current applications of nanomaterials in urinary system tumors - Qian, Zhounan; Zhang, Yang; Yuan, Jie; Gong, Sun; Chen, Binghai (Frontiers in Bioengineering and Biotechnology, 2023)
The development of nanotechnology and nanomaterials has provided insights into the treatment of urinary system tumors. Nanoparticles can be used as sensitizers or carriers to transport drugs. Some nanoparticles have intrinsic therapeutic effects on tumor cells. Poor patient prognosis and highly drug-resistant malignant urinary tumors are worrisome to clinicians. The application of nanomaterials and the associated technology against urinary system tumors offers the possibility of improving treatment. At present, many achievements have been made in the application of nanomaterials against urinary system tumors. This review summarizes the latest research on nanomaterials in the diagnosis and treatment of urinary system tumors and provides novel ideas for future research on nanotechnologies in this field.